Board independence and firm performance: Evidence from Bangladesh - Afzalur Rashid (Future Business Journal, 2018)
This study examines whether board independence influences firms' economic performance among listed firms in Bangladesh. By using data from 135 listed firms on Dhaka Stock Exchange and by using accounting and market performance measures, this study uses simultaneous equation approach to control the potential endogeniety problem. This study finds that, board independence and firm economic performance does not positively influence each other. This study also finds that, board size has significant positive influence on both board independence and firm performance. These findings raise the questions of whether "one size fits all" type corporate governance practices can be exercised around the world. Bangladesh has imitated the requirement of having outside directors sit on corporate boards to make corporate boards independent and accountable, ignoring the underlying institutional differences. While board independence is an important attribute of corporate board practices in many developed countries, board independence still may be an illusion in Bangladesh.
Keywords: 650; Agency theory; Bangladesh; Board independence; CEO; Power; Stewardship theory